The Paradoxical Aesthetics of Kawih Wanda Anyaran by Mang Koko - Riza Windyagiri, Sony; Herdini, Heri; Suparli, Lili (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
This research analyzes the aesthetics of Kawih Wanda Anyaran by Mang Koko via the lens of Paradox Aesthetics as articulated by Jakob Sumardjo. Paradox Aesthetics posits that the allure of Nusantara art emerges from the tension between two ostensibly contradictory aspects that finally converge into harmony. This research utilizes a qualitative method with an ethnomusicological approach to analyze the lyrical, musical, and social contextual elements of Kawih Wanda Anyaran. The results identify four principal types of paradox: tradition–modernity, simplicity–complexity, individuality–collectivity, and rationality–emotionality. These paradoxes form a unique artistic basis, as Mang Koko adeptly showcases musical innovation while being deeply rooted in Sundanese cultural traditions. Kawih Wanda Anyaran exemplifies the intricate interplay among the artist, the community, and the encompassing cultural milieu. These findings affirm that Mang Koko's compositions function as expressions of musical creativity and as embodiments of paradoxical aesthetics, which hold substantial importance for arts education, cultural preservation, and the progression of Sundanese karawitan studies in contemporary and future contexts. This study provides a conceptual contribution to comprehending how paradox aesthetics can function as a framework for interpreting traditional musical compositions and presents avenues for additional research on aesthetic alterations within Nusantara Arts.